2017
DOI: 10.1002/em.22111
|View full text |Cite
|
Sign up to set email alerts
|

A study of DNA damage in buccal cells of consumers of well‐ and/or tap‐water using the comet assay: Assessment of occupational exposure to genotoxicants

Abstract: Because of concerns that natural aquifers in the region of Todos Santos (Baja California Sur, Mexico) might be contaminated by organochlorine pesticides and heavy metals, a case-control study was conducted among consumers and non-consumers of well- and/or tap-water to determine risks to human health. This study was based on a genotoxic evaluation of buccal cells using the Comet assay technique. Levels of DNA damage in the consumers group were significantly higher than those of the control group. However, occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Similarly, a total of 11 studies investigated the genotoxic effect of chemicals or drugs (legal or illegal) on the oral mucosa, such as: nandrolone decanoate (29), pesticides (30), car paints (31) and anti-neoplastic drugs (32). Vasquez-Boucard et al postulated harmful effects of continuous exposure to water/tap water contaminated by organochlorine pesticides and heavy metals in Mexico (33). By contrast, the authors failed to establish a dose-response relationship between pollution and genotoxicity on oral mucosa cells (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a total of 11 studies investigated the genotoxic effect of chemicals or drugs (legal or illegal) on the oral mucosa, such as: nandrolone decanoate (29), pesticides (30), car paints (31) and anti-neoplastic drugs (32). Vasquez-Boucard et al postulated harmful effects of continuous exposure to water/tap water contaminated by organochlorine pesticides and heavy metals in Mexico (33). By contrast, the authors failed to establish a dose-response relationship between pollution and genotoxicity on oral mucosa cells (33).…”
Section: Resultsmentioning
confidence: 99%
“…Vasquez-Boucard et al postulated harmful effects of continuous exposure to water/tap water contaminated by organochlorine pesticides and heavy metals in Mexico (33). By contrast, the authors failed to establish a dose-response relationship between pollution and genotoxicity on oral mucosa cells (33). Other pollutants have been investigated, such as air pollution (34), and other settings such as occupational exposure of airport personnel (35) and battery renovation workers (36).…”
Section: Resultsmentioning
confidence: 99%
“…As we explained, buccal cell samples are much easier to obtain and less invasive than blood sampling. Vazquez Boucard et al (2017), demonstrated with the comet assay in 107 male buccal samples that people who drank well water or tap water rich in organochlorine pesticides and heavy metals detected in Todos Santos, BCS, Mexico presented elevated levels of DNA damage [59].…”
Section: Alkaline Comet Assaymentioning
confidence: 99%
“…DNA damage, as determined by the mean comet tail length, was high in women exposed to pesticides while picking cotton with bare hands, and a positive correlation of DNA damage with age and exposure time was observed (Ali et al 2017). The comet assay showed that occupational exposure to pesticides was more dangerous than consumption of contaminated water, which was greater than controls; this difference between exposed and unexposed groups was not influenced by other factors, such as age or smoking or alcohol habits (Vazquez Boucard et al 2017). The comet assay can also be useful in monitoring DNA damage in single cells due to exposure to chemotherapy and radiotherapy in cancer patients or to assess the cancer chemoprevention of some molecules (Santoro et al 2016).…”
mentioning
confidence: 91%